2005
DOI: 10.1002/pd.1341
|View full text |Cite
|
Sign up to set email alerts
|

First-trimester fetal nuchal translucency and inherited metabolic disorders

Abstract: NT appears to have a limited role in identifying affected fetuses in pregnancies at high risk for inherited metabolic disorders. NT may be normal in early pregnancy even for fetuses affected with conditions known to be associated with non-immune hydrops fetalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…There was no family history of the inherited disorder. According to reports [ 20 ] stating, some inherited metabolic disorders have increased nuchal thickness in the first trimester, and doctors tested the parents to identify whether they were carriers of c.1492C>T (p.R498W). GT was performed on the woman and her husband to exclude the possibility of their carrying c.1492C>T in VPS33A .…”
Section: Resultsmentioning
confidence: 99%
“…There was no family history of the inherited disorder. According to reports [ 20 ] stating, some inherited metabolic disorders have increased nuchal thickness in the first trimester, and doctors tested the parents to identify whether they were carriers of c.1492C>T (p.R498W). GT was performed on the woman and her husband to exclude the possibility of their carrying c.1492C>T in VPS33A .…”
Section: Resultsmentioning
confidence: 99%
“…They observed 13 fetuses afflicted with Gaucher disease, glycogenosis type II, mucopolysaccharidosis type I, Krabbe disease, metachromatic leukodystrophy, mucopolysaccharidosis type II, NPD-A, Pelizaeus–Merzbacher disease, and sialidosis, and concluded that an increased NT was found only in one fetus with trisomy 21 but without mucopolysaccharidosis type II. Thus, the NT in early pregnancy might be normal even in fetuses afflicted with conditions known to be associated with non-immune hydrops fetalis ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of extracellular matrix could explain this finding in inherited metabolic disorders (Von Kaisenberg et al , ). However, in a large reported series, including 66 fetuses at high risk for inherited metabolic disorders, this association was not observed, and the single affected fetus by Hunter syndrome showed a normal NT (De Biasio et al , ), stressing again the need for larger sample studies.…”
Section: Discussionmentioning
confidence: 99%